Aboriginal art - Caruana, Wally (London Thames and Hudson, 1993)
Survey of the work of Australia's indigenous artists which shows how the events of the Dreaming and their significance are embodied in artistic works covering a wide range of media from painting and sculpture to printmaking and textile design. Features numerous colour and black-and-white plates, a bibliography, a list of illustrations, a glossary and an index. The author has been the curator of Aboriginal Art at the Australian National Gallery since 1984.
Ch. 1. Introduction -- Ch. 2. Patterns of power: Arnhem Land and its surrounds -- Ch. 3. The art of place and journey: the desert -- Ch. 4. Land of the Wandjina: the Kimberley -- Ch. 5. Diversity: North Queensland and the Torres Strait Islands -- Ch. 6. Artists in the town and city.
187 illustrations, 31 in colour
Includes bibliographical references (page 209) and indexes.
Keywords: Art, Australian aboriginal